Pre-emptive Analgesia: A Comparative Study between Ilioinguinal-Iliohypogastric Combined Nerve Block and Incision Line Local Anaesthetic Infiltration in Paediatric Inguinal Hernia Repair (The Planet, 2022)
Background: Painful interventions may have serious adverse physical and psychological impact in children. Acute postoperative pain is one of the most adverse stimuli experienced by children. In the paediatric age group pain is most often remain under-treated. Acute postoperative pain following open inguinal hernia repair is maximum during the first 24 hours. In order to reduce this significant postoperative pain various modalities are currently being used. Ilioinguinal-iliohypogastric combined nerve block and incision line infiltration with local anaesthetics is being performed to reduce pain intensity postoperatively which is easy to perform, cost effective and are associated with less adverse effects. The present study was aimed to evaluate & compare pre-emptive ilioinguinal-iliohypogastric combined nerve block and surgical incision line local anaesthetic infiltration for management of postoperative pain in paediatric inguinal hernia repair. Methodology:  This randomized control trial which was carried out in 60 paediatric patients scheduled for inguinal hernia repair under general anaesthesia (GA) in Dhaka Medical College and Hospital, Dhaka. The study population were divided randomly into two groups having 30 patients in each. Group A received 1mg/kg of 0.25% bupivacaine for surgical incision line infiltration and group B received 1mg/kg of 0.25% bupivacaine for pre-emptive ilioinguinal-iliohypogastric combined nerve block with USG guidance, then following parameters had been recorded and compared between two groups: intensity of pain by FLACC Behavioural Pain Assessment Scale, time of first analgesic requirement and the consumption of total amount of rescue analgesics in first 24 hours and postoperative adverse effects. After pre anaesthetic check-up & discussion about study procedures written informed consent was taken from the legal guardians. Separate case record form was used in each case. Data analysis was done by SPSS version 26. The demographic profile was well matched in both groups (p>0.05). Mean duration of analgesia for group A was 127.4±13.6 minutes and for group B was 356.42±20.62 minutes, (p
Keywords: Ilioinguinal-iliohypogastric nerve block; incision line infiltration; pre-emptive analgesia; inguinal hernia repair; postoperative pain; bupivacaine; children